Engaging inquiry : research and writing in the disciplines - KIRSCHT, Judy; Mark Schlenz (New Jersey : Prentice Hall, 2002)
Arming students with the tools they will need to successfully produce and communicate in a university environment, this highly practical text offers an in-depth, fully integrated study of inquiry and writing processes-showing students how to think and write across the interdisciplinary board, and empowering them with real skills they can use and develop on a daily basis. While acknowledging analytical processes common to all research thinking and writing, it blends a variety of reading and writing activities that help students explore specific disciplines, different aspects of those processes, and how the full range of thinking and writing skills can develop best through inquiry within disciplinary contexts. Moving from writing in the sciences to the social sciences, humanities, and finally critical applications of interdisciplinary thinking, it employs a process approach, sequenced readings, hands-on inquiry and informal writing activities.
Includes bibliography and index
Keywords: x; Research -- Methodology; Interdisciplinary approach in education